Multi-component synthesis and invitro biological assessment of novel pyrrole derivatives and pyrano[2,3-c]pyrazole derivatives using Co3O4 nanoparticles as recyclable nanocatalyst - Almeleebia, Tahani M.; Jasim Naser, Mokhtar; Saeed, Shakir Mahmood; Abid, Majeed M.; Altimari, Usama S.; Shaghnab, Murtadha Laftah; Rasen, Fadhil A.; Alawadi, Ahmed; Ahmad, Irfan; Alsalamy, Ali (Frontiers in Materials, 2024)
In this study, Co3O4 nanoparticles were used as nanocatalyst for two different series of nitrogen-containing heterocyclic compounds, including pyrrole (Pyo) derivatives and pyrano [2,3-c]pyrazole (Pya[2,3-c]Pyz) derivatives. In the synthesis of derivatives, using 15 mol% and 10 mol% of the catalyst for Pyo derivatives and Pya[2,3-c]Pyz derivatives, respectively, an efficiency between 83-96%, were observed . In addition, novel derivatives of Pyo and Pya[2,3-c]Pyz were synthesized and their structures were confirmed. In general, the advantages of using cobalt nanoparticles compared to previous reports include the synthesis of new derivatives, lower temperature used in the synthesis of derivatives, shorter synthesis time and high efficiency.The biological properties of the synthesized products, such as antibacterial, antifungal, and antioxidant properties, were tested and investigated. In antibacterial and antifungal tests, IZD, MIC, MBC, and MFC were measured and reported. In antioxidant activity, IC50 was calculated and reported. High reusability, green and environmentally friendly, synthesis of new derivatives and synthesis of products with higher efficiency and shorter time were the important benefits of using cobalt nanoparticles as a catalyst. In antioxidant tests, the IC50 for synthesized Pyo derivatives and Pya[2,3-c]Pyz derivatives were between 12.2-13.71 μg/mL, and 16.18-17.75 μg/mL, respectively. In antimicrobial testes, the MIC for synthesized Pyo derivatives and Pya[2,3-c]Pyz derivatives were between 2-4096 μg/mL, and 2-2048 μg/mL, respectively. The results showed that the antioxidant property of Pyo derivatives were more than Pya[2,3-c]Pyz derivatives, but the antimicrobial effect of Pya[2,3-c]Pyz derivatives were more than Pyo derivatives. The antioxidant results proved that the activity of Pyo derivatives and Pya[2,3-c]Pyz derivatives does not depend on the substitutions of the derivatives and is close to each other. Therefore, based on this, a proposed mechanism for stability of DPPH by Pyo derivatives and Pya[2,3-c]Pyz derivatives were suggested. Finally, based on the more stable resonance structures of Pyo derivatives, compared to Pya[2,3-c]Pyz derivatives, its high antioxidant property was justified. Pya[2,3-c]Pyz derivatives has 2 heterocyclic rings connected together )pyrano and pyrazole), but Pyo derivatives has only one heterocyclic ring (pyrrole). So high antimicrobial property of Pya[2,3-c]Pyz derivatives compared to Pyo derivatives can be attributed to having two bioactive heterocyclic rings.